The surface-sulphurated Co3O4 nanowire array electrocatalyst for oxygen evolution reaction and water-splitting applications. Issue 2 (23rd December 2022) - Li, Junwei; Wang, Yige; Liu, Wenwei; Liang, Zhenyi; Fan, Chunlei; Li, Jinying; Luo, Shengxu; Nan, Haoxiong; Yu, Jia
Abstract : A surface-sulphurated cobalt oxide electrocatalyst with a nanowire array integrated structure is designed for oxygen evolution reaction and water-splitting applications. Abstract : With the aggravation of the environmental pollution problem and the depletion of natural resources, hydrogen production based on water splitting technology has become an effective method to satisfy the increasing demand for renewable energy. It is vital to design high-efficiency and low-cost electrocatalysts for water splitting. Herein, an electrocatalyst (Co3 O4 –S/NF) with a surface-sulphurated nanowire array structure is controllably synthesized for catalysing the oxygen evolution reaction (OER) process. Co3 O4 –S/NF (1 : 0.5) exhibits the best OER activity with an overpotential of 297 mV at 100 mV cm −2, which is lower than the overpotential (331 mV) of commercial Ir/C/NF. Additionally, the water-splitting voltage of the Co3 O4 –S/NF//Pt/C/NF electrolyzer reaches 1.571 V at 20 mV cm −2, which is also better than that of conventional noble-metal electrocatalysts. Notably, Co3 O4 –S/NF//Pt/C/NF also shows excellent efficiency in seawater electrolysis. The voltage reaches 1.656 V in a simulated alkaline seawater electrolyte (1 M KOH + 0.5 M NaCl) and 1.722 V in an alkaline seawater electrolyte (1 M KOH in seawater). This work can provide a robust electrocatalyst design for water electrolysis.